2021
DOI: 10.1177/20552076211033428
|View full text |Cite
|
Sign up to set email alerts
|

Affecting factors of cloud computing adoption in public hospitals affiliated with Zahedan University of Medical Sciences: A cross-sectional study in the Southeast of Iran

Abstract: Objective Health care organizations require cloud computing to remain efficient and cost-effective, and provide high-quality health care services. Adoption of this technology by users plays a critical role in the success of its application. This study aimed to determine factors affecting cloud computing adoption in public hospitals affiliated with Zahedan University of Medical Sciences. Methods A cross-sectional descriptive and analytic study was performed in 2017. The study population comprised information te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Since CCA adoption in major cities of KSA is more under the decisive control of decisionmakers. In addition to TOE factors and their sub-influencing factors, as mentioned in recent research [27], human factors were also identified among the most influential factors. The mean value of human factors was reported as 3.27 ± 0.63 which is smaller than the mean value of environmental factors.…”
Section: Discussionmentioning
confidence: 94%
“…Since CCA adoption in major cities of KSA is more under the decisive control of decisionmakers. In addition to TOE factors and their sub-influencing factors, as mentioned in recent research [27], human factors were also identified among the most influential factors. The mean value of human factors was reported as 3.27 ± 0.63 which is smaller than the mean value of environmental factors.…”
Section: Discussionmentioning
confidence: 94%
“…Previous works are always a source of inspiration. Several previous studies have been done in the cloud computing and medical fields and there must have been certain ways in which previous studies would have been conducted [ [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] ] . This segment throws light on such studies and provides a background on how this study will merge the breeding technology of cloud computing with the continuous evolution of medical science.…”
Section: Literature Surveymentioning
confidence: 99%
“…ALIPOUR et al [ 25 ] focused on building a questionnaire for healthcare workers regarding their opinions on the use of technology in public and private hospitals in Iran. They distributed seven hundred questionnaires with questions relating to technology in sections like security, complexity, costs, and compatibility; questions relating to organizational benefits referring to relative advantage, management support, and resource adequacy; and finally, questions on governmental policies and cognitive approach.…”
Section: Literature Surveymentioning
confidence: 99%
“…However, despite the increased attention given to cloud computing in various disciplinary domains such as disease monitoring, health surveillance, and clinical diagnosis, there is a lack of research on the cloud migration of HISs. A comprehensive review of the PubMed and HuiyiMd databases only yielded 3 relevant studies: an Iranian study that identified key driving factors for hospitals adopting cloud computing [ 10 ], a Greek study that proposed a method for migrating clinical and laboratory data based on local hospital conditions [ 11 ], and an American study that focused on essential considerations for chief financial officers before venturing into the cloud [ 12 ]. However, none of these studies have adequately addressed the aforementioned issue.…”
Section: Introductionmentioning
confidence: 99%